Field emission characteristics and analysis of chargé flow through graphite based cathodes - Allaham, Mohammad M.; Burda, Daniel; Sobola, Dinara; Knápek, Alexandr (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2023)
This paper studies the performance of differenttypes of graphite cathodes when operated as field emissionelectron sources. The tested cathodes were prepared in theform of bulk polymer graphite, bulk pure graphite, and polymergraphite coated with thin layer of insulating material(epoxy resin). The obtained results include X-Ray photoelectronspectroscopy analysis, scanning electron micrographs, the fieldemission microscope patterns and current-voltage characteristics,and the orthodoxy test analysis results. The importance of thisstudy is summarized in following the pursuit of finding cheapand green electron sources. Moreover, to present a new exoticfield emission behavior in the form of emission pulses.
Keywords: field emission; pulsed field emission; graphite,microflakes; polymer graphite